Lagierniczki : dziesiec lat w polarnym kraju - Zawadzka, Jadwiga (Warszawa : Oficyna Wydawnicza Volumen, 1991)
A account of 10 years spent in a Russian work camp as a prisoner, from 1945 to 1955.
Includes index.
Keywords: Zawadzka, Jadwiga; World War, 1939-1945 -- Deportations from Poland; Polish people -- Soviet Union -- Biography; World War, 1939-1945 -- Personal narratives, Polish; Concentration camps -- Soviet Union